2004
DOI: 10.1007/s10493-004-0201-y
|View full text |Cite
|
Sign up to set email alerts
|

Response of soil mites to organic cultivation in an ultisol in southeast Brazil

Abstract: Soil-dwelling mites of four plots under organic management were investigated in April and December 1998 and in December 1999. Their populations were compared with mite populations in a pasture and forest in the vicinity. It was observed that there was always an initial reduction in the populations of soil mites and in the activity of the epigeic forms whenever a plot was opened up and disturbed mechanically in preparation for cultivation, irrespective of previous organic inputs. With time, the densities and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…This finding agrees with Badejo and Akinyemiju (1993) and Aktar et al (2009) who reported that application of pesticide led to the reduction of micro-arthropods population in soil. It is also consistent with Badejo et al (2004) who proved that herbicide Atrazine greatly reduced acarid species richness, abundance, and diversity in soil.…”
Section: Resultssupporting
confidence: 90%
“…This finding agrees with Badejo and Akinyemiju (1993) and Aktar et al (2009) who reported that application of pesticide led to the reduction of micro-arthropods population in soil. It is also consistent with Badejo et al (2004) who proved that herbicide Atrazine greatly reduced acarid species richness, abundance, and diversity in soil.…”
Section: Resultssupporting
confidence: 90%
“…Bettiol et al 2002;Van Leeuwen et al 2015) and more soil microarthropods were found in organically managed farming systems than in conventional ones. Oribatida reacted positively to organic management, together with Uropodina (Badejo et al 2004). However, in apple orchards that were permanent crop, there was no significant difference in density of oribatid mites between the organic and conventional management (Doles et al 2001).…”
Section: Introductionmentioning
confidence: 96%
“…Due to their morpho-ecological features they can live in forest floor litter, on the soil surface, in various soil horizons. Active nutrition of oribatids in floor litter and soil horizons with dead plant tissues provides soil enrichment with organic compounds and products of decomposition, influencing the soil's water-air properties and connected with successional changes in ecosystem (Badejo, 2004;Bird et al, 2004). Oribatid mites are one of few groups of soil saprophages which have the ability to consume coniferous litter (Striganova, 1980;Sylvain & Buddle, 2010).…”
Section: Introductionmentioning
confidence: 99%